Covid-19 pandemic and the meaning of life: an educational intervention (Emancipação, 2023)
His study aimed to understand the perspectives of the meaning of life linked to the educational context during the COVID-19 pandemic. Fifteen professionals of a state public school in the city of João Pessoa-Paraíba participated in the intervention, being 3 second grade teachers, 9 High School teachers, 2 principals and 1 professional from the Administrative Sector of the School. The ages ranged from 27 to 63 years (M=41.2, SD=10.97), mostly Catholic and female. Its theoretical perspective was Logotherapy and Existential Analysis, therapy through meaning. The perspectives of the meaning of life were understood from three main elements: 1) Attitudes of school professionals towards the pandemic moment; 2) Considerations about self-perception and self-perception of life; and 3) Considerations about the meaning of life. Thus, it was possible to highlight the human characteristic of self-transcendence of existence that was more accentuated during the pandemic time.
Keywords: Logotherapy and Existential Analysis; Self-transcendence; Educational Context; Pandemic Time